Information technology for the development and analysis of models of subject areas for their study - Lyubchenko, V.V. (Інститут програмних систем НАН України, 2015)
The paper describes the information technology of domain models design and analysis for their study. The basic concepts of information technology – abstraction, association and adaptation – are defined. Domain information model, domain content model and domain associative map are built on basis of basic concepts. Using of these models for assessing the quality of the domain model is described.